Between Repetition and Occasion. A Gadamerian Contribution to Everyday Aesthetics - Romagnoli, Elena (Scenari, 2023)
In this paper I aim to focus on a possible contribution of Gadamer’s aesthetics in the line of inquiries of Everyday Aesthetics, stressing the continuistic and anti-exceptionalist perspective at the core of Gadamerian philosophy. I will show how it is possible to highlight the continuity between artistic experience and everyday life in the critique of “aesthetic differentiation”, in order to explain how Gadamer could contribute to the so called “expansive” approach of Everyday Aesthetics. In particular, I will tackle the concepts of repetition and occasion. The former manifests the characteristic proper to every form of art, namely being iterable in a way that does not contradict its uniqueness. The concept of occasion draws attention on the specificity of every aesthetic experience, manifesting its “extraordinary” character within ordinary life.